10 questions concerning sustainable building renovation. (1st October 2018) - Jensen, Per Anker; Maslesa, Esmir; Berg, Jakob Brinkø; Thuesen, Christian
Abstract: In countries all over Europe the need for building renovation is receiving increased attention. One reason for this is an ageing building stock. Another reason is the need for more environmentally sustainable buildings with reductions in energy consumption and greenhouse gas emissions to limit the harmful climate impact. There is at the same time a need to upgrade many buildings to improve the quality of life – social sustainability, for instance improve indoor climate; and to increase productivity in the building process to ensure affordable housing – economic sustainability. Low productivity and frequent conflicts in the construction sector have led to an increasing interest in new forms of collaboration between the different stakeholders involved in construction projects. Development of strategic partnerships concerning a portfolio of renovation projects are seen as a promising way to achieve more sustainable building renovation for some large building clients and for companies with a high maturity in collaborative practice. There is a large number of tools for design decision support and systems for sustainability certification of buildings, but there are not many tools and systems dedicated to building renovation. Measuring the different dimensions of sustainability is a challenge. Regulations play a central role in opening the markets for sustainable building renovation through incentive schemes, building codes, etc. Although traditional approaches to energy renovation emphasize more efficient heating and lighting systems and better insulation, there is a tendency to address the challenge more holistically by emphasizing social targets. Highlights: Seven characteristics distinguish building renovation from a new building project. There are not many tools and systems dedicated to planning building renovation. Strategic partnerships can be a promising way to achieve more sustainable building renovation. Regulations play a central role in opening the markets for sustainable building.